2015
DOI: 10.1124/mol.115.100594
|View full text |Cite
|
Sign up to set email alerts
|

Axon-to-Glia Interaction Regulates GABAAReceptor Expression in Oligodendrocytes

Abstract: Myelination requires oligodendrocyte-neuron communication, and both neurotransmitters and contact interactions are essential for this process. Oligodendrocytes are endowed with neurotransmitter receptors whose expression levels and properties may change during myelination. However, only scant information is available about the extent and timing of these changes or how they are regulated by oligodendrocyte-neuron interactions. Here, we used electrophysiology to study the expression of ionotropic GABA, glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 45 publications
7
76
1
1
Order By: Relevance
“…This transient innervation is concomitant to the temporal expression window of the γ2 subunit of GABA A receptors (γ2‐GABA A Rs) in OPCs (Balia et al, ), a subunit preferentially expressed at unitary synaptic connections between parvalbumin (PV)‐expressing fast‐spiking interneurons and OPCs (Orduz et al, ). Along the oligodendrocyte lineage, γ2 expression is restricted to the OPC stage (Zhang et al, ; Arellano et al, ) and γ2‐GABA A Rs are exclusively located at OPC postsynaptic sites (Balia et al, ; Orduz et al, ; Passlick et al, ). In this report, we induced a loss‐of‐function of γ2‐GABA A Rs in OPCs to test whether γ2‐mediated synaptic signaling affects OPC dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This transient innervation is concomitant to the temporal expression window of the γ2 subunit of GABA A receptors (γ2‐GABA A Rs) in OPCs (Balia et al, ), a subunit preferentially expressed at unitary synaptic connections between parvalbumin (PV)‐expressing fast‐spiking interneurons and OPCs (Orduz et al, ). Along the oligodendrocyte lineage, γ2 expression is restricted to the OPC stage (Zhang et al, ; Arellano et al, ) and γ2‐GABA A Rs are exclusively located at OPC postsynaptic sites (Balia et al, ; Orduz et al, ; Passlick et al, ). In this report, we induced a loss‐of‐function of γ2‐GABA A Rs in OPCs to test whether γ2‐mediated synaptic signaling affects OPC dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is the first demonstration that GAT‐1 is expressed in oligodendrocytes, our findings are not surprising given the known relationships between GABA and oligodendrocytes (Hamilton et al, in press; Verkhratsky and Butt, ). Functional GABA A R have been demonstrated in oligodendrocyte progenitor cells (OPCs) and in oligodendrocytes (Arellano et al, ; Berger et al, ; Kirchhoff and Kettenmann, ; Lin and Bergles, ; Vélez‐Fort et al, ; Von Blankenfeld et al, ), and GABAergic synapses from neurons are known to contact OPCs (Lin and Bergles, ; Tanaka et al, ). In addition, GABA B R are expressed by OPCs, and are down‐regulated in myelinating oligodendrocytes (Charles et al, ; Luyt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed that the sensitivity to GABA of mature OLs is greatly diminished compared to OPCs, suggesting a specific regulation of GABA A R expression during OL lineage cell development (Figure b; Arellano et al, ; Berger, Walz, Schnitzer, & Kettenmann, ; Von Blankenfeld, Trotter, & Kettenmann, ). Concerning the OL mature state, Arellano et al () recently observed that GABA A R‐mediated responses also drastically decreases with time in isolated OL cultures, while the presence of neurons in cocultures allows for maintaining their functional expression. A direct interaction between neurons and OLs seems therefore necessary to stabilize GABA A Rs in differentiated cells.…”
Section: Gaba In Neuron–oligodendroglia Communicationmentioning
confidence: 91%
“…However, the neuron‐to‐OL signals involved in this process remain unknown. Blockade of neuronal activity with the Na + channel blocker TTX does not change OLs sensitivity to GABA, suggesting that a basal neuronal activity is not required to keep GABA A R functional expression (Arellano et al, ).…”
Section: Gaba In Neuron–oligodendroglia Communicationmentioning
confidence: 99%